2016
DOI: 10.1186/s40795-016-0078-2
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with underweight status in children under five: an analysis of the 2010 Rwanda Demographic Health Survey (RDHS)

Abstract: Background: Under-nutrition contributes to childhood morbidity and mortality, particularly in low-income countries. While Rwanda is one of few countries on track to reduce the prevalence of underweight children under five years old by 50 % from 1990 to 2015 (a target of Millennium Development Goal1), underweight children remain a large public health problem with one out of ten children having low weight-for-age. Methods: We performed a cross-sectional study using 2010 RDHS data on 4177 children under five year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
37
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 20 publications
15
37
0
3
Order By: Relevance
“…This is in line with previous related studies in Philippines(44), Libya (45), Ethiopia (17), Uganda (46), Mozambique (47), and Ghana (42). The reason was stated in different literatures; educated women are better informed about optimal child care practices (48), have better practices in terms of hygiene (49,50) feeding (51),and childcare during illness (51)(52)(53), have a greater ability to use the health system (54), are more empowered to make decisions (49). However, the majority (65%) of sampled households' did not attend formal education as a result knowledge of mothers on child care may not be enough.…”
Section: Discussionsupporting
confidence: 87%
“…This is in line with previous related studies in Philippines(44), Libya (45), Ethiopia (17), Uganda (46), Mozambique (47), and Ghana (42). The reason was stated in different literatures; educated women are better informed about optimal child care practices (48), have better practices in terms of hygiene (49,50) feeding (51),and childcare during illness (51)(52)(53), have a greater ability to use the health system (54), are more empowered to make decisions (49). However, the majority (65%) of sampled households' did not attend formal education as a result knowledge of mothers on child care may not be enough.…”
Section: Discussionsupporting
confidence: 87%
“…Given the negative impact of stunting on individual growth, socio-economic development, and achieving the sustainable development goals, effective programs to reduce stunting must be developed. Although many malnutrition-related studies have been conducted in various countries, only one study was in Rwanda identifying the risk factors associated with being underweight (Mukabutera, et al, 2016). In order to design effective programs to further reduce stunting, understanding the risk factors associated with stunting specific to Rwanda is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…The latest Rwanda Demographic and Health Survey (RDHS 2014-15) found that teenage pregnancy rate had increased from 4.1% in 2005 to 7.3% in 2015, with the rate in some regions reaching as high as 15.8% (National Institute of Statistics of Rwanda (NISR), Ministry of Health (MOH) [Rwanda], 2015). While many studies have used DHS data to study risk factors related to antenatal care, postnatal care, fertility, and nutrition (Manzi et al, 2014;Mukabutera et al, 2016;Ndahindwa et al, 2014), none have studies those related to teenage pregnancies in Rwanda. Accordingly, this study utilized a secondary data analysis method to identify the risk factors contributing to teenage pregnancies in Rwanda.…”
Section: Introductionmentioning
confidence: 99%